The sacrifice of Sunshine Girl - McKenzie, Paige; Ohlin, Nancy (McKenzie, Paige. Haunting of Sunshine girl, 2018)
Sunshine Griffith, a luiseach who talks to ghosts and is a benevolent spirit guide for humans, must determine who or what is working against her and the other luiseach.